Nanocrystalline soft magnetic powder core with low stress sensitivity and preparation method
By designing alloy components and combining the preparation process, the positive correlation between the magnetostrictive coefficient and stress sensitivity of the nanocrystal soft magnetic powder core is solved, and the problem of stress sensitivity of nanocrystal soft magnetic materials in the prior art is solved, and the problem of stress sensitivity of nanocrystal soft magnetic materials is realized. Nanocrystal soft magnetic powder core with high permeability, low loss and low stress sensitivity is used.
Patent Information
- Application Number
- CN202411580342.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-11
Smart Images

Figure CN119419027A_ABST
Abstract
Description
[Technical field]
[0001] The invention relates to the technical field of magnetic materials, and in particular to a nanocrystalline soft magnetic powder core with low stress sensitivity and a preparation method thereof. [Background technology]
[0002] Soft magnetic materials play a key role in both power conversion and electronics. Among them, iron-based amorphous and nanocrystalline alloys have attracted increasing attention in the efficient distribution of energy due to their unique microstructure, low magnetic anisotropy constant, high magnetic permeability and saturation flux density, low coercivity and low core loss.
[0003] In most applications, soft magnetic materials are fixed on devices or surrounded by coils, and some are even filled with glue, which will generate additional external assembly stress. For crystalline ferromagnetic materials, their magnetocrystalline anisotropy is much larger than the magnetoelastic coupling energy, and this type of small stress has little effect on the magnetic properties. However, amorphous / nanocrystalline alloys have small magnetocrystalline anisotropy and high magnetoelastic coupling coefficient, which makes amorphous / nanocrystalline alloys very sensitive to stress, and even slight stress can have a significant effect on their magnetic properties. Therefore, the preparation of iron-based amorphous / nanocrystalline alloys with stress-insensitive properties is very necessary in practical applications.
[0004] The deterioration of magnetic properties under stress is mainly due to the stress-induced additional anisotropy caused by magnetoelastic coupling properties, also known as magnetoelastic anisotropy. Magnetoelastic anisotropy is usually negatively correlated with the magnetostriction coefficient of the material. Generally speaking, reducing the magnetostriction of the material and the corresponding stress-induced anisotropy to zero is an effective way to suppress its stress sensitivity. However, this is not the case for amorphous / nanocrystalline alloys; in nanostructured systems, the magnetoelastic anisotropy related to the structural correlation length is averaged, resulting in only one isotropic magnetostriction coefficient in each domain; this situation is opposite to traditional large-grained alloys, where the magnetostriction of traditional large grains is anisotropic, usually represented by λ. 100 and λ 111 Definition, corresponding to the easy magnetization direction and the hard magnetization direction. Therefore, the saturation magnetostriction coefficient λ in the traditional sense s =(2λ 100 +3λ 111 ) / 5 is zero, it does not mean that the corresponding nanocrystalline alloy has low stress sensitivity, which also increases the difficulty of developing nanocrystalline soft magnetic materials with low stress sensitivity.
[0005] The Chinese invention patent with publication number CN107267889 discloses an iron-based amorphous alloy with low stress sensitivity, which reduces stress sensitivity by adjusting the ratio of the three elements of the FeSiB amorphous alloy, and indeed obtains a lower magnetic property deterioration index under stress, but the Fe-Si-B amorphous alloy has a much higher loss than the nanocrystalline alloy due to the limitation of the intrinsic composition, and the iron-based amorphous alloy is a strip magnetic core, which is not suitable for use at high frequencies. The Chinese invention application with publication number CN118237585 discloses a method for reducing the internal stress of a soft magnetic composite material and its annealing device, but it can only reduce the internal stress by annealing, and cannot eliminate the external stress, such as the influence of assembly stress. Therefore, it is urgent to develop a soft magnetic material with high magnetic permeability, low loss, and low stress sensitivity. [Summary of the invention]
[0006] The technical problem to be solved by the present invention is to provide a nanocrystalline soft magnetic powder core with low stress sensitivity and a preparation method thereof. The prepared nanocrystalline soft magnetic powder core has the characteristics of high magnetic permeability, low loss and low stress sensitivity.
[0007] The present invention is achieved in that:
[0008] In a first aspect, a nanocrystalline soft magnetic powder core with low stress sensitivity, wherein the alloy composition of the nanocrystalline soft magnetic powder core is Fe a Si b B c Cu d C e M f , where a, b, c, d, e, and f are the atomic percentage contents of the corresponding elements, 70≤a≤80, 10≤b≤20, 5≤c≤10, 0.5≤d≤2, 0≤e≤2, 0≤f≤5, and a+b+c+d+e+f=100; M is a transition metal element with a large atomic radius.
[0009] Furthermore, the atomic percentage content of Si and B is controlled within 18≤b+c≤25.
[0010] Furthermore, M is one or more of Ti, V, Cr, Mn, Zr, Nb, Mo, Hf, Ta, and W.
[0011] In a second aspect, a method for preparing a nanocrystalline soft magnetic powder core with low stress sensitivity comprises the following steps:
[0012] Step 1, material preparation: weigh the raw materials according to the alloy composition of the soft magnetic powder core;
[0013] Step 2, atomization powder making: the weighed raw materials are melted into molten metal, slag-making agent and deoxidizer are added during the smelting process, and after deoxidation, water-gas combined atomization is used for high-pressure atomization powder making; after the powder making is completed, the obtained amorphous magnetic powder is dried and sieved in turn to obtain amorphous soft magnetic powder of target particle size;
[0014] Step 3, insulation coating: prepare a passivating agent, place the amorphous soft magnetic powder in the passivating agent and keep stirring to react, and dry after the reaction is completed; add the dried amorphous soft magnetic powder into an acetone solution dissolved with epoxy resin and mechanically stir, and dry after the acetone evaporates to obtain the coated amorphous soft magnetic powder;
[0015] Step 4, pressing and molding: the coated amorphous soft magnetic powder is fully mixed with a zinc stearate release agent, and cold pressed to obtain an amorphous powder core green body;
[0016] Step 5, heat treatment: placing the amorphous powder core green body in an atmosphere protection furnace and maintaining it at a preset temperature for stress relief crystallization heat treatment, and cooling it with the furnace after the heat treatment, thereby obtaining a nanocrystalline soft magnetic powder core.
[0017] Furthermore, in step 2, the content of the slag-forming agent is 0.1-1wt% of the total weight of the raw materials, and the content of the deoxidizer is 0.1-0.5wt% of the total weight of the raw materials.
[0018] Furthermore, in step 2, the target particle size of the amorphous soft magnetic powder is 1-30 μm.
[0019] Furthermore, in step 3, the passivator is a phosphoric acid / ethanol solution, and the phosphoric acid content of the phosphoric acid / ethanol solution is 0.1-1wt% of the weight of the amorphous soft magnetic powder; the amorphous soft magnetic powder is placed in the passivator and kept stirring for 1.5 hours to react.
[0020] Furthermore, in step 3, the content of the epoxy resin in the acetone solution is 2 to 5 wt % of the weight of the amorphous soft magnetic powder.
[0021] Furthermore, in step 4, the content of the zinc stearate release agent is 0.1-0.5wt% of the weight of the amorphous soft magnetic powder; and the pressing force of the cold pressing molding is 600-2000MPa.
[0022] Furthermore, in step 5, the preset temperature is 400-550° C., and the insulation time is 0.5-3 hours.
[0023] By adopting the technical solution of the present invention, at least the following beneficial effects are achieved:
[0024] 1. The problem of the irrelevance of magnetostriction coefficient and stress sensitivity in traditional amorphous / nanocrystalline alloys has been overcome. Anisotropy is reintroduced in the preparation of soft magnetic powder cores to build a positive correlation between the magnetostriction coefficient and stress sensitivity of the material. By cleverly designing the ratio of amorphous / nanocrystalline alloy components, using zero magnetostriction components, and further combining the preparation processes of atomization powder making, insulation coating, pressing and stress relief annealing, nanocrystalline soft magnetic powder cores with high magnetic permeability, low loss and low stress sensitivity can be well prepared.
[0025] 2. The nanocrystalline soft magnetic powder core prepared by the present invention has a small change in magnetic permeability and low loss under the action of external stress, and can be well used as an inductor element such as filtering, current stabilization and energy storage on various switching power supply modules.
Brief Description of the Drawings
[0026] The present invention will be further described below in conjunction with embodiments with reference to the accompanying drawings.
[0027] Figure 1 It is a principle block diagram of a method for preparing a nanocrystalline soft magnetic powder core with low stress sensitivity of the present invention;
[0028] Figure 2 It is the magnetostriction detection diagram of Example 1 and Comparative Example 1 in the present invention;
[0029] Figure 3 is a magnetic permeability detection diagram of Example 1 of the present invention before and after external stress is applied;
[0030] Figure 4 It is a magnetic permeability detection diagram of comparative example 1 in the present invention before and after applying external stress. [Specific implementation method]
[0031] The specific embodiments of the present invention will be described in more detail below with reference to the accompanying drawings. Although the specific embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to enable the scope of the present invention to be fully communicated to those skilled in the art.
[0032] It should be noted that certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that technicians may use different nouns to refer to the same component. This specification and claims do not use the difference in nouns as a way to distinguish components, but use the difference in the functions of the components as the criterion for distinction. As mentioned throughout the specification and claims, "including" or "comprising" is an open term, so it should be interpreted as "including but not limited to". The subsequent description of the specification is a preferred embodiment of the present invention, but the description is based on the general principles of the specification and is not intended to limit the scope of the present invention. The scope of protection of the present invention shall be determined by the attached claims.
[0033] The soft magnetic powder core is a soft magnetic composite material prepared by powder metallurgy by mixing soft magnetic powder and insulating medium. The particle size of the magnetic powder usually used in the iron-based nanocrystalline soft magnetic powder core is no more than 50μm. After being prepared into a composite material, the orientation of each magnetic powder is anisotropic, making the magnetostriction of the composite material as a whole also anisotropic.
[0034] Therefore, the present invention prepares a composite material (i.e., a nanocrystalline soft magnetic powder core) through alloy composition design, powder making, coating, pressing and annealing; wherein, the orientation of each magnetic powder in the powder core is anisotropic, so that the magnetostriction of the powder core as a whole is also anisotropic, thereby constructing a positive correlation between the stress sensitivity of the powder core and the magnetostriction; a nanocrystalline soft magnetic powder core with zero magnetostriction and low stress sensitivity can be obtained by only controlling the alloy composition.
[0035] In nanocrystalline alloys, the intrinsic magnetostriction coefficient of the amorphous matrix is about 23ppm, while the intrinsic magnetostriction coefficient of the precipitated α-Fe is about -6ppm. The overall magnetostriction coefficient of the nanocrystalline alloy is the sum of the magnetostriction coefficients of these two items multiplied by the corresponding volume fractions. Therefore, it is necessary to precipitate as much α-Fe as possible in the nanocrystalline alloy to adjust the magnetostriction coefficient to near zero. In the subsequent preparation of the powder core, some additional inorganic insulating materials will be introduced. Such materials have no magnetism and usually have a magnetostriction coefficient of 0, which can dilute the magnetostriction of the nanocrystalline alloy as a whole. In addition, the resin used as a binder is also elastic, so it can absorb the slight volume expansion of the magnetic powder under the magnetic field. In this case, even if the magnetostriction value of the original component alloy is not strictly close to 0, the magnetostriction value of the obtained powder core as a whole can be close to zero. Not only can a nanocrystalline soft magnetic powder core with low stress sensitivity be obtained, but also the composition range can be broadened, while reducing the Si / B content and increasing the Fe content, so as to obtain high saturation.
[0036] The invention discloses a nanocrystalline soft magnetic powder core with low stress sensitivity, wherein the alloy composition of the nanocrystalline soft magnetic powder core is Fe aSi b B c Cu d C e M f , where a, b, c, d, e, and f are the atomic percentage contents of the corresponding elements, 70≤a≤80, 10≤b≤20, 5≤c≤10, 0.5≤d≤2, 0≤e≤2, 0≤f≤5, and a+b+c+d+e+f=100; M is a transition metal element with a large atomic radius.
[0037] In some embodiments of the present invention, the atomic percentage content of Si and B is controlled within 18≤b+c≤25. In the specific implementation, in order to offset the positive magnetostriction of the amorphous phase, a large volume of negative magnetostrictive α-Fe(Si) should be formed in the amorphous matrix; and increasing the Si content can increase the precipitation of α-Fe(Si) during the crystallization process, thereby obtaining near-zero magnetostriction; in addition, increasing the content of Si and B can also improve the amorphous forming ability, making it easier to obtain magnetic powder with a high amorphous rate during the powder making process, and at the same time can increase the resistivity of the magnetic powder and reduce the powder core loss; however, excessive introduction of non-magnetic elements will reduce magnetic saturation and magnetic permeability, so the present invention controls the atomic percentage content of Si and B within 18≤b+c≤25, so that the total content of Si and B elements will not be too high or too low, which is conducive to obtaining near-zero magnetostriction and reducing powder core loss, and will not reduce magnetic saturation and magnetic permeability.
[0038] Since the solid solubility of the Cu element in the face-centered cubic structure is low in the body-centered cubic iron, clusters will occur preferentially, and such clusters will reduce the nucleation activation energy, and serve as nucleation sites for Fe to promote the precipitation of α-Fe(Si), so it is essential to add a small amount of Cu to the nanocrystals; but when the Cu content is too high, it will promote the precipitation of the Fe-B phase, thereby deteriorating the soft magnetic properties. Therefore, in order to better promote the precipitation of α-Fe(Si) without deteriorating the soft magnetic properties, the present invention controls the atomic percentage content of Cu to 0.5≤d≤2.
[0039] In amorphous alloys, adding C elements with small atomic radius can effectively increase the entropy value, thereby improving the amorphous forming ability, making it easier to obtain high amorphous magnetic powder during the powder making process and improving the overall soft magnetic properties; therefore, the present invention adds C elements with an atomic percentage content of 0≤e≤2.
[0040] In some embodiments of the present invention, M is one or more of Ti, V, Cr, Mn, Zr, Nb, Mo, Hf, Ta, and W. At the same time, transition metal elements with large atomic radius can effectively inhibit the coarsening of nanocrystals and reduce coercivity, thereby obtaining more excellent soft magnetic properties; therefore, the present invention adds transition metal elements M with large atomic radius in an atomic percentage content of 0≤f≤5.
[0041] See also Figure 1 As shown, the present invention provides a method for preparing a nanocrystalline soft magnetic powder core with low stress sensitivity, the preparation method comprising the following steps:
[0042] Step 1: Prepare the materials: weigh the raw materials according to the alloy composition of the soft magnetic powder core, that is, according to the alloy composition Fe designed above. a Si b B c Cu d C e M f Weigh the raw materials.
[0043] Step 2, atomization powder making: the weighed raw materials are melted into molten metal, slag-forming agent and deoxidizer are added during the smelting process, and after deoxidation, water-gas combined atomization is used for high-pressure atomization powder making; after the powder making is completed, the obtained amorphous magnetic powder is dried and sieved in turn to obtain amorphous soft magnetic powder of the target particle size; among them, water-gas combined atomization powder making is an advanced metal powder preparation technology, which combines the advantages of gas atomization and water atomization, and can produce ultrafine and spherical powder materials.
[0044] Step 3, insulation coating: prepare a passivating agent, place the amorphous soft magnetic powder in the passivating agent and keep stirring to react, and dry after the reaction is completed; add the dried amorphous soft magnetic powder into an acetone solution dissolved with epoxy resin and mechanically stir, and dry after the acetone evaporates to obtain the coated amorphous soft magnetic powder;
[0045] Step 4, pressing and molding: the coated amorphous soft magnetic powder is fully mixed with a zinc stearate release agent, and cold pressed to obtain an amorphous powder core green body;
[0046] Step 5, heat treatment: placing the amorphous powder core green body in an atmosphere protection furnace and maintaining it at a preset temperature for stress relief crystallization heat treatment, and cooling it with the furnace after the heat treatment, thereby obtaining a nanocrystalline soft magnetic powder core.
[0047] In some embodiments of the present invention, in step 2, the content of the slag-forming agent is 0.1-1wt% of the total weight of the raw materials, and the content of the deoxidizer is 0.1-0.5wt% of the total weight of the raw materials. Adding a deoxidizer during smelting in air can effectively remove trace oxygen in the raw materials. In the smelting process of nanocrystalline alloys, a small amount of Si is usually added as a deoxidizer. If an excessive amount is added, it will melt in the alloy and affect the composition. Therefore, the present invention controls the content of the deoxidizer to 0.1-0.5wt%. At the same time, adding a slag-forming agent during smelting can reduce the melting point of the slag and increase the slag formation rate, thereby effectively removing impurities. Usually, a small amount of slag-forming agent can be added to achieve the effect.
[0048] In some embodiments of the present invention, since the particle size of the magnetic powder in the iron-based nanocrystalline soft magnetic powder core is not easy to be too large, in step 2, the target particle size of the amorphous soft magnetic powder is controlled to be 1-30 μm.
[0049] In some embodiments of the present invention, in step 3, the passivator is a phosphoric acid / ethanol solution, and the phosphoric acid content of the phosphoric acid / ethanol solution is 0.1 to 1 wt% of the weight of the amorphous soft magnetic powder, wherein the phosphoric acid / ethanol solution refers to a solution formed by dissolving phosphoric acid in ethanol. By using the phosphoric acid / ethanol solution as a passivator to phosphate the amorphous soft magnetic powder, a layer of water-insoluble phosphate protective film can be generated on the surface of the amorphous soft magnetic powder; the amorphous soft magnetic powder is placed in the passivator and kept stirring for 1.5 hours to react to ensure that the amorphous soft magnetic powder can be fully phosphated.
[0050] In some embodiments of the present invention, in step 3, the content of epoxy resin in the acetone solution is 2-5wt% of the weight of the amorphous soft magnetic powder. In the present invention, the acetone solution in which epoxy resin is dissolved is used as a binder. If the content of epoxy resin in the binder is too little, the magnetic ring is prone to cracking after external stress is applied during use. Therefore, the content of epoxy resin in the present invention is controlled to be 2-5wt%.
[0051] In some embodiments of the present invention, in step 4, the content of the zinc stearate release agent is 0.1-0.5wt% of the weight of the amorphous soft magnetic powder. In the present invention, zinc stearate is used as a lubricant and a release agent to improve lubricity and reduce viscosity. Only a small amount of addition is required to improve powder fluidity, which is beneficial to increase density during the pressing process. In order to better press-form the mixed amorphous soft magnetic powder and the zinc stearate release agent, in step 4, the pressing force of the cold pressing is 600-2000MPa.
[0052] In some embodiments of the present invention, in order to better achieve stress relief annealing, in step 5, the preset temperature is 400-550°C, and the insulation time is 0.5-3 hours. For nanocrystalline soft magnetic powder cores, annealing is to remove the internal stress caused by pressing and molding on the one hand, and to precipitate fine nanocrystalline grains in the amorphous matrix on the other hand; the annealing temperature of nanocrystalline soft magnetic powder cores is usually determined according to the crystallization temperature of different components, and the annealing time should not be too long, otherwise the α-Fe(Si) nanocrystalline particles will be coarsened and the Fe-B phase harmful to the soft magnetic properties will be precipitated.
[0053] By adopting the above technical solution of the present invention, at least the following beneficial effects are achieved:
[0054] 1. The problem of the irrelevance of magnetostriction coefficient and stress sensitivity in traditional amorphous / nanocrystalline alloys has been overcome. Anisotropy is reintroduced in the preparation of soft magnetic powder cores to build a positive correlation between the magnetostriction coefficient and stress sensitivity of the material. By cleverly designing the ratio of amorphous / nanocrystalline alloy components, using zero magnetostriction components, and further combining the preparation processes of atomization powder making, insulation coating, pressing and stress relief annealing, nanocrystalline soft magnetic powder cores with high magnetic permeability, low loss and low stress sensitivity can be well prepared.
[0055] 2. The nanocrystalline soft magnetic powder core prepared by the present invention has a small change in magnetic permeability and low loss under the action of external stress, and can be well used as an inductor element such as filtering, current stabilization and energy storage on various switching power supply modules.
[0056] To facilitate understanding of the present invention, further explanation will be given below by taking specific embodiments as examples in conjunction with the accompanying drawings, and each of the accompanying drawings does not constitute a limitation on the embodiments of the present invention.
[0057] Example 1
[0058] Design of amorphous / nanocrystalline alloy composition Fe 74 Si 15 B7Nb3Cu1, weigh and melt the industrial raw materials according to the designed alloy composition, add 0.5wt% slag-making agent and 0.5wt% deoxidizer at the same time, let the raw materials stand for slag removal after stable melting, and use water-gas combined atomization for high-pressure atomization powder making after deoxidation. After the powder making is completed, the obtained amorphous magnetic powder is dried and sieved in turn to obtain amorphous soft magnetic powder with a particle size of 1 to 30μm; then take an appropriate amount of amorphous soft magnetic powder, and select phosphoric acid / ethanol solution as a passivator, the phosphoric acid content of the phosphoric acid / ethanol solution is 0.5wt% of the weight of the amorphous soft magnetic powder, place the amorphous soft magnetic powder in the passivator and keep stirring for 1.5 hours for phosphating, and dry after the reaction. The amorphous soft magnetic powder after phosphating and drying is added to an acetone solution dissolved with epoxy resin and mechanically stirred, the content of epoxy resin in the acetone solution is 3wt% of the weight of the amorphous soft magnetic powder, and the coated amorphous soft magnetic powder is dried after the acetone evaporates. Subsequently, the coated amorphous soft magnetic powder is fully mixed with a zinc stearate release agent, the content of the zinc stearate release agent is 0.3wt% of the weight of the amorphous soft magnetic powder, and cold pressed at 1600MPa, and demolded to obtain an amorphous powder core green body. Finally, the amorphous powder core green body is placed in an atmosphere protection furnace and kept at 540°C for 1 hour for stress relief crystallization heat treatment, and after the treatment is completed, it is cooled in the furnace to finally obtain a nanocrystalline soft magnetic powder core with low stress sensitivity.
[0059] Example 2
[0060] Design of amorphous / nanocrystalline alloy composition Fe 73 Si15 B8Ti3Cu1, weigh and melt the industrial raw materials according to the designed alloy composition, add 0.5wt% slag-making agent and 0.5wt% deoxidizer at the same time, stand and slag after the raw materials are stably melted, and use water-gas combined atomization for high-pressure atomization powder making after deoxidation. After the powder making is completed, the obtained amorphous magnetic powder is dried and sieved in turn to obtain amorphous soft magnetic powder with a particle size of 1 to 30μm; then take an appropriate amount of amorphous soft magnetic powder, and select phosphoric acid / ethanol solution as a passivator, the phosphoric acid content of the phosphoric acid / ethanol solution is 0.5wt% of the weight of the amorphous soft magnetic powder, place the amorphous soft magnetic powder in the passivator and keep stirring for 1.5 hours for phosphating, and dry after the reaction. The phosphated and dried amorphous soft magnetic powder is added to an acetone solution dissolved with epoxy resin and mechanically stirred, the content of epoxy resin in the acetone solution is 3wt% of the weight of the amorphous soft magnetic powder, and the coated amorphous soft magnetic powder is dried after the acetone evaporates. Subsequently, the coated amorphous soft magnetic powder is fully mixed with a zinc stearate release agent, the content of the zinc stearate release agent is 0.3wt% of the weight of the amorphous soft magnetic powder, and cold pressed at 1600MPa, and demolded to obtain an amorphous powder core green body. Finally, the amorphous powder core green body is placed in an atmosphere protection furnace and kept at 480°C for 1 hour for stress relief crystallization heat treatment, and after the treatment is completed, it is cooled in the furnace to finally obtain a nanocrystalline soft magnetic powder core with low stress sensitivity.
[0061] Example 3
[0062] Design of amorphous / nanocrystalline alloy composition Fe 76 Si 14B5C1Nb3Cu1, weigh and smelt the industrial raw materials according to the designed alloy composition, add 0.5wt% slag-making agent and 0.5wt% deoxidizer at the same time, stand and slag after the raw materials are stably melted, and use water-gas combined atomization to perform high-pressure atomization powder making after deoxidation. After the powder making is completed, the obtained amorphous magnetic powder is dried and sieved in turn to obtain amorphous soft magnetic powder with a particle size of 1 to 30μm; then take an appropriate amount of amorphous soft magnetic powder, and select phosphoric acid / ethanol solution as a passivator, the phosphoric acid content of the phosphoric acid / ethanol solution is 0.5wt% of the weight of the amorphous soft magnetic powder, place the amorphous soft magnetic powder in the passivator and keep stirring for 1.5 hours for phosphating, and dry after the reaction. The amorphous soft magnetic powder after phosphating and drying is added to an acetone solution dissolved with epoxy resin and mechanically stirred, the content of epoxy resin in the acetone solution is 3wt% of the weight of the amorphous soft magnetic powder, and the coated amorphous soft magnetic powder is dried after the acetone evaporates. Subsequently, the coated amorphous soft magnetic powder is fully mixed with a zinc stearate release agent, the content of the zinc stearate release agent is 0.3wt% of the weight of the amorphous soft magnetic powder, and cold pressed at 1600MPa, and demolded to obtain an amorphous powder core green body. Finally, the amorphous powder core green body is placed in an atmosphere protection furnace and kept at 520°C for 1 hour for stress relief crystallization heat treatment, and after the treatment is completed, it is cooled in the furnace to finally obtain a nanocrystalline soft magnetic powder core with low stress sensitivity.
[0063] like Figure 2 , Figure 3 As shown in the following Table 1, Table 1 is a performance table of the nanocrystalline soft magnetic powder cores prepared in Examples 1 to 3 (including effective magnetic permeability, loss, magnetostriction, and magnetic permeability attenuation under an external stress of 20 MPa); Figure 2 The magnetostriction detection diagrams of Example 1 and Comparative Example 1 of the present invention are shown in FIG. Figure 3 The following is a magnetic permeability test diagram of Example 1 of the present invention before and after the external stress is applied. The effective magnetic permeability μ of the sample at 100 kHz is measured by a broadband LCR tester. e The magnetostriction coefficient of the sample was determined by the resistance method; the power analyzer was used to measure the sample at f = 100kHz, B m =Total loss at 100mT.
[0064] Table 1 Performance of the prepared nanocrystalline soft magnetic powder core
[0065]
[0066] It can be seen from Table 1 above that by adopting the technical solution of the present invention, a nanocrystalline soft magnetic powder core with zero magnetostriction or near-zero magnetostriction can be effectively obtained, and the attenuation degree of the magnetic permeability of the nanocrystalline soft magnetic powder core under external stress can be minimized, that is, it has low stress sensitivity and the advantages of high magnetic permeability and low loss. It can be used as an inductor element such as filtering and energy storage on various switching power supply modules.
[0067] Comparative Example 1
[0068] The preparation method of Comparative Example 1 is exactly the same as that of Example 1, except that the alloy component selected in Comparative Example 1 is Fe 77 Si6B 13 Nb3Cu1. Figure 2 and Figure 4 As shown in the figure, due to the low Si content in the alloy composition, the α-Fe content generated in the subsequent crystallization process is small, not only the soft magnetic properties are deteriorated, but also the magnetic permeability decays greatly under external stress. After actual measurement, the magnetic permeability of the nanocrystalline soft magnetic powder core prepared in Comparative Example 1 is 40 at a frequency of 100kHz; under the conditions of 100kHz and 0.1T, the loss is as high as: 1250mW / cm 3 ; The magnetostriction coefficient is 10ppm, and the magnetic permeability decays by as much as 23.5% when external stress is applied, and the magnetic permeability cannot be stably maintained at high frequencies, such as MHz.
[0069] Comparative Example 2
[0070] The preparation method of Comparative Example 2 is exactly the same as that of Example 1, except that the alloy component selected in Comparative Example 2 is Fe 77 Si 15 B7Cu1. Although the alloy composition has a high Si content, the α-Fe nanocrystalline particles generated in the subsequent crystallization process are severely coarsened due to the lack of atoms with large radius, which seriously deteriorates the soft magnetic properties. At the same time, the degree of magnetic permeability attenuation is high under external stress. It has been measured that the magnetic permeability of the nanocrystalline soft magnetic powder core prepared in Comparative Example 2 is 23 at a frequency of 100kHz; at 100kHz, 0.1T, the loss is as high as: 1430mW / cm 3 ; The magnetostriction coefficient is 4ppm, and the magnetic permeability decays by 11% when external stress is applied.
[0071] Comparative Example 3
[0072] The preparation method of Comparative Example 3 is exactly the same as that of Example 1, except that the content of epoxy resin in the selected binder is 1 wt %. Due to the small amount of added binder, although the magnetic ring can be formed after pressing, it will directly crack and break after applying external stress, which is not conducive to practical application.
[0073] Although the specific implementation modes of the present invention are described above, those skilled in the art should understand that the specific implementation modes described are only illustrative and are not intended to limit the scope of the present invention. Equivalent modifications and changes made by those skilled in the art in accordance with the spirit of the present invention should be included in the scope of protection of the claims of the present invention.
Claims
1. A nanocrystalline soft magnetic powder core with low stress sensitivity, characterized in that: The alloy composition of the nanocrystalline soft magnetic powder core is Fe a Si b B c Cu d C e M f , where a, b, c, d, e, and f are the atomic percentage contents of the corresponding elements, 70≤a≤80, 10≤b≤20, 5≤c≤10, 0.5≤d≤2, 0≤e≤2, 0≤f≤5, and a+b+c+d+e+f=100; M is a transition metal element with a large atomic radius.
2. A nanocrystalline soft magnetic powder core with low stress sensitivity as claimed in claim 1, characterized in that: The atomic percentage content of Si and B is controlled within 18≤b+c≤25.
3. A nanocrystalline soft magnetic powder core with low stress sensitivity as claimed in claim 1, characterized in that: The M is one or more of Ti, V, Cr, Mn, Zr, Nb, Mo, Hf, Ta, and W.
4. A method for preparing a nanocrystalline soft magnetic powder core with low stress sensitivity as claimed in any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: Step 1, material preparation: weigh the raw materials according to the alloy composition of the soft magnetic powder core; Step 2, atomization powder making: the weighed raw materials are melted into molten metal, slag-making agent and deoxidizer are added during the smelting process, and after deoxidation, water-gas combined atomization is used for high-pressure atomization powder making; after the powder making is completed, the obtained amorphous magnetic powder is dried and sieved in turn to obtain amorphous soft magnetic powder of target particle size; Step 3, insulation coating: prepare a passivating agent, place the amorphous soft magnetic powder in the passivating agent and keep stirring to react, and dry after the reaction is completed; add the dried amorphous soft magnetic powder into an acetone solution dissolved with epoxy resin and mechanically stir, and dry after the acetone evaporates to obtain the coated amorphous soft magnetic powder; Step 4, pressing and molding: the coated amorphous soft magnetic powder is fully mixed with a zinc stearate release agent, and cold pressed to obtain an amorphous powder core green body; Step 5, heat treatment: placing the amorphous powder core green body in an atmosphere protection furnace and maintaining it at a preset temperature for stress relief crystallization heat treatment, and cooling it with the furnace after the heat treatment, thereby obtaining a nanocrystalline soft magnetic powder core.
5. The method for preparing a nanocrystalline soft magnetic powder core with low stress sensitivity according to claim 4, characterized in that: In step 2, the content of the slag-forming agent is 0.1-1wt% of the total weight of the raw materials, and the content of the deoxidizer is 0.1-0.5wt% of the total weight of the raw materials.
6. The method for preparing a nanocrystalline soft magnetic powder core with low stress sensitivity according to claim 4, characterized in that: In step 2, the target particle size of the amorphous soft magnetic powder is 1-30 μm.
7. The method for preparing a nanocrystalline soft magnetic powder core with low stress sensitivity according to claim 4, characterized in that: In step 3, the passivator is a phosphoric acid / ethanol solution, and the phosphoric acid content of the phosphoric acid / ethanol solution is 0.1-1wt% of the weight of the amorphous soft magnetic powder; the amorphous soft magnetic powder is placed in the passivator and stirred for 1.5 hours to react.
8. The method for preparing a nanocrystalline soft magnetic powder core with low stress sensitivity according to claim 4, characterized in that: In step 3, the content of the epoxy resin in the acetone solution is 2-5 wt % of the weight of the amorphous soft magnetic powder.
9. The method for preparing a nanocrystalline soft magnetic powder core with low stress sensitivity according to claim 4, characterized in that: In step 4, the content of the zinc stearate release agent is 0.1-0.5wt% of the weight of the amorphous soft magnetic powder; and the pressing force of the cold pressing molding is 600-2000MPa.
10. The method for preparing a nanocrystalline soft magnetic powder core with low stress sensitivity according to claim 4, characterized in that: In step 5, the preset temperature is 400-550° C., and the insulation time is 0.5-3 hours.